BROAD-BAND AND WIDE DYNAMIC-RANGE SEISMIC OBSERVATIONS WITH AN STS-SEISMOGRAPH AT SYOWA STATION, EAST ANTARCTICA - カナオ, マサキ; カミヌマ, カツタダ; KANAO, Masaki; KAMINUMA, Katsutada (National Institute of Polar Research, 1994)
P(論文) Broad-band and wide dynamic-range seismic observations with a three-component Streckeisen seismometer (STS-1V, -1H) have been carried out at Syowa Station, East Antarctica since April 1989. A digital acquisition system for broad-band (BRB) velocity signals was started from May 1990,for the purpose of providing valuable data for the study of global seismology. In this paper, the seismic observations with STS are presented during the winter period of the 33rd Japanese Antarctic Research Expedition (JARE-33; from February 1992 to January 1993). In practice, the current observation system, hypocentral distribution of the detected events and some examples of recorded digital waveforms are presented. A possibility to detect a weak long-period signal, such as that of the free oscillation of the Earth, is also mentioned in relation to the observations with the superconducting gravimeter at Syowa Station which have been carried out since March 1993. departmental bulletin paper